Mast cells in the developing avian eye - Girol, Ana Paula; Oliani, Sonia Maria [UNESP]; Smith, Ricardo Luiz (My University, 1996)
Mast cells are present in the eye of Gallus domesticus, appearing in the anterior uvea in embryos at stage 39 HH (13th day). In hatching and adult birds, they are present in the sciera, uvea, pectinate ligament, and conjunctiva. Mast cells are absent in the cornea, retina, and pecten oculi. Maturing mast cells in the anterior eye segment appear as round cells having eccentric nuclei and a few cytoplasmic metachromatic granules, whose fluorescence increases during development. Mature cells are more numerous in late development, and their cytoplasm is rich in metachromatic and intensely fluorescent granules. Ultrastructurally, maturing mast cells display progranules and a few electron dense and homogeneous granules on one side of the cell. Mast cells of adult birds possess homogeneous cytoplasmic granules, some of which display protuberances that penetrate hollows of adjoining granules. Heterogeneous granules exhibiting latticed and mottled patterns are also present. The existence of mast cells in the anterior eye segment indicates that these cells might perform a physiological role during development and in aqueous humor outflow. They might modulate exchanges between blood and aqueous humor through chemical mediators present in their granules. © 1996 Wiley-Liss, Inc.